1992
DOI: 10.1111/j.1754-7121.1992.tb00696.x
|View full text |Cite
|
Sign up to set email alerts
|

Policy process perceptions of senior Canadian federal civil servants: a view of the state and its environment

Abstract: Based on interviews with senior civil federal civil servants in Ottawa, perceptions of various actors' influence on public policy are examined. It is hypothesized that perceived influence patterns will change as one moves across the major phases of the policy process. Although it is expected that actors within the state will be of primary importance throughout the process, it is also expected that the relative importance of actors outside the state will increase as one moves from forming a policy agenda and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Studies undertaken by federal government analysts, however, raised doubts about this picture (French 1980; Hartle 1978). Later studies, in the 1990s, also noted the growth and subsequent decline of employment of policy analysts in government and their limited capacity for developing long‐term strategic advice to governments (Bennett and McPhail 1992; Hollander and Prince 1993). Work since the early 1990s has suggested that tasks of policy analysts may be shifting, as in the U.K. and the other countries cited above, towards an increased emphasis on policy process design and network management activities and away from “formal” types of policy analysis (Howlett and Lindquist 2004; Lindquist 1992).…”
Section: Assessing Policy Analytical Capacity In Practicementioning
confidence: 99%
“…Studies undertaken by federal government analysts, however, raised doubts about this picture (French 1980; Hartle 1978). Later studies, in the 1990s, also noted the growth and subsequent decline of employment of policy analysts in government and their limited capacity for developing long‐term strategic advice to governments (Bennett and McPhail 1992; Hollander and Prince 1993). Work since the early 1990s has suggested that tasks of policy analysts may be shifting, as in the U.K. and the other countries cited above, towards an increased emphasis on policy process design and network management activities and away from “formal” types of policy analysis (Howlett and Lindquist 2004; Lindquist 1992).…”
Section: Assessing Policy Analytical Capacity In Practicementioning
confidence: 99%
“…Recent examinations of components of policy advisory systems such as political parties (Cross, 2007), the media (Murray, 2007) and partisan appointees (OECD, 2011; Connaughton, 2010b, Eichbaum and Shaw, 2010), among others, have underlined the limitations of locational models in being able to provide an exhaustive map of policy advice system types and a clear picture of how the various sources, types and components of policy advice fit together and operate (Mayer, Bots and van Daalen, 2004; Howlett and Lindquist, 2004). What is needed is a better model that links the provision of advice to larger patterns of changes in the behaviour of political decision-makers and knowledge suppliers that condition how policy advice is generated and deployed in different governance arrangements (Peled, 2002; Howlett and Lindquist, 2004; Bevir and Rhodes, 2001; Bevir, Rhodes and Weller, 2003; Aberbach and Rockman, 1989; Bennett and McPhail, 1992). Such a richer understanding of the structure and functioning of policy advisory systems can be obtained through the better specification of the second, “content”, dimension highlighted in Halligan's work and clarification of its relationship to locational considerations of influence.…”
Section: Adding the Content Dimension To Locational Models Of Policy mentioning
confidence: 99%
“…Different types of “policy advice systems” exist depending on the nature of knowledge supply and demand in a particular sector or jurisdiction, and what analysts do in brokering information, how they do it, and with what effect, depends in large part on the type of advisory system present in the area in which they work (Noordegraaf, 2010). This helps to explain why different styles of policy analysis can be found in different policy fields (Howlett & Lindquist, 2004; Mayer, Bots, & van Daalen, 2004) since these can be linked to larger patterns of behavior of political actors and knowledge suppliers that condition how policy advice is generated and deployed (Aberbach & Rockman, 1989; Bennett & McPhail, 1992; Bevir & Rhodes, 2001; Bevir, Rhodes, & Weller, 2003; Peled, 2002).…”
Section: Policy Advice Systems In Modern Governmentsmentioning
confidence: 99%